Attitudes towards STEM education: nonlinear effects of teachers’ readiness and the crucial role of affective conditions - Vaiopoulou, Julie; Papagiannopoulou, Theano; Stamovlasis, Dimitrios (Frontiers in Education, 2024)
Introduction Teacher attitudes (Att) toward STEM—Science, Technology, Engineering, and Mathematics—education is decisive for its successful integration into contemporary curricula. On the other hand, teachers’ readiness for STEM influences their attitudes and controls their behavior in everyday practice. Methods In this study, the four dimensions of readiness for STEM, i.e., affective conditions (Affe), cognitive preparedness (Cogn), self-efficacy (SEff), and STEM commitment (Com), measured via the TRi-STEM scale, were tested as predictors of attitudes using non-linear models. Data were taken from teachers (N = 494) who completed the TRi-STEM questionnaire and the attitudes towards STEM scale for measuring attitudes. Catastrophe theory was applied, and three cusp models, superior to the linear and logistic counterparts, were proposed predicting attitudes (Att) as a function of combinations of Cogn, SEff, Com, and Affe. Results The three models are as follows: Cusp 1 with (Cogn – Affe) as asymmetry and (Cogn + Affe) as bifurcation factors; Cusp 2 with (Com – Affe) as asymmetry and (Com + Affe) as bifurcation factors, and Cusp 3 with (SEff – Affe) as asymmetry and (SEff + Affe) as bifurcation factors. The findings showed that affective conditions involved in a dynamic interplay with other independent variables could lead to sudden and abrupt changes in Att. Discussion The empirical evidence for non-linear effects in teacher attitudes (Att) toward STEM informs theory development and practice by supporting the complexity and dynamical system framework as a more realistic premise to describe and interpret potentially occurring phenomena of teachers’ behavior in the context of STEM education.